Biographical predictors of learnership performance in the South African fruit packing industry - Nicholaas Singleton, Nicholaas Singleton (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2010.